The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.14744/anatoljcardiol.2017.7628
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of early use of tolvaptan in very elderly patients with acute decompensated heart failure

Abstract: Objective:The establishment of an optimal strategy for elderly patients with acute decompensated heart failure (ADHF) is currently an important issue. Particularly in very elderly (VE) patients, ADHF is associated with a poor prognosis. We therefore aimed to evaluate the efficacy and safety of the early use of tolvaptan (TLV) in VE patients.Methods:Of 245 patients with ADHF admitted between March 2013 and July 2014, we prospectively enrolled 111 patients with TLV first administered within 24 h of hospitalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 30 publications
4
10
0
Order By: Relevance
“…Kinoshita and colleagues demonstrated that tolvaptan therapy in patients aged over 80 years old with repeated HF hospitalizations resulted in immediate decongestion and reduced hospitalization period with a lower incidence of worsening renal function [22]. In another study, patients aged over 85 years old had similar rate of worsening renal function and length of hospitalization stay compared with those aged under 85 years old during tolvaptan therapy [23].…”
Section: Elderly Populationsmentioning
confidence: 99%
“…Kinoshita and colleagues demonstrated that tolvaptan therapy in patients aged over 80 years old with repeated HF hospitalizations resulted in immediate decongestion and reduced hospitalization period with a lower incidence of worsening renal function [22]. In another study, patients aged over 85 years old had similar rate of worsening renal function and length of hospitalization stay compared with those aged under 85 years old during tolvaptan therapy [23].…”
Section: Elderly Populationsmentioning
confidence: 99%
“…The treatment of ADHF in the (very) elderly can be particularly difficult due to advanced age-related frailty and comorbidities increasing the odds for a poor outcome, deterioration of liver and kidney function predisposing to inadequate drug metabolism or elimination, reduced efficacy, and increased risk of drug toxicity, or other adverse events. In this regard, this study ( 11 ) is reassuring in that, regardless of age, tolvaptan represents a safe therapy for patients with ADHF. More specifically, tolvaptan use in doses and duration as used in the study performed by Niikura et al ( 11 ) does not increase the risk of WRF, a relatively common side effect of drug therapy in patients with ADHF that portends a poor prognosis ( 12 ).…”
mentioning
confidence: 71%
“…In this regard, this study ( 11 ) is reassuring in that, regardless of age, tolvaptan represents a safe therapy for patients with ADHF. More specifically, tolvaptan use in doses and duration as used in the study performed by Niikura et al ( 11 ) does not increase the risk of WRF, a relatively common side effect of drug therapy in patients with ADHF that portends a poor prognosis ( 12 ). Moreover, the study may be unique in addressing the treatment of ADHF in such a high-risk and difficult to treat group of patients as are the very elderly.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…We were very interested to read the article entitled ’The clinical utility of early use of tolvaptan in very elderly patients with acute decompensated heart failure’ by Niikura et al ( 1 ) recently published in the Anatol J Cardiol 2017; 18: 206-12 and the editorial comment entitled ’Tolvaptan in the very elderly with acute decompensated heart failure- a therapeutic option worth of consideration’ by Ndrepepa ( 2 ) in the same issue, which evaluated the safety and efficacy of tolvaptan, a selective vasopressin V2 receptor antagonist, in very elderly patients.…”
mentioning
confidence: 99%